Ferrichrome Has Found Its Match: Biomimetic Analogues with Diversified Activity Map Discrete Microbial Targets. Issue 53 (31st August 2017) - Besserglick, Jenny; Olshvang, Evgenia; Szebesczyk, Agnieszka; Englander, Joseph; Levinson, Dana; Hadar, Yitzhak; Gumienna‐Kontecka, Elzbieta; Shanzer, Abraham
Abstract: Siderophores provide an established platform for studying molecular recognition principles in biological systems. Herein, the preparation of ferrichrome (FC) biomimetic analogues varying in length and polarity of the amino acid chain separating between the tripodal scaffold and the pendent Fe III chelating hydroxamic acid groups was reported. Spectroscopic and potentiometric titrations determined their iron affinity to be within the range of efficient chelators. Microbial growth promotion and iron uptake studies were conducted on E. coli, P. putida and U. maydis . A wide range of siderophore activity was observed in the current series: from a rare case of a species‐specific growth promotor in P. putida to an analogue matching FC in cross‐phylum activity and uptake pathway. A fluorescent conjugate of the broad‐range analogue visualized siderophore destination in bacteria (periplasmic space) vs. fungi (cytosol) mapping new therapeutic targets. Quantum dots (QDs) decorated with the most potent FC analogue provided a tool for immobilization of FC‐recognizing bacteria. Bacterial clusters formed around QDs may provide a platform for their selection and concentration. Abstract : Ferrying Ferric : A "true" analogue matching ferrichrome (FC) in cross‐phylum activity, uptake pathway, and iron affinity is described. This fluorescently labeled analogue sheds light on the fate of siderophores following iron delivery and provides a tool for identifying microbial targets. Quantum dots (QD) decorated with this analogue trigger cluster formation by FC‐recognizing bacteria, suggesting a method for microbial concentration and separation (see scheme).